The Kinetics Studies on Hydrolysis of Hemicellulose - Yuan, Qi; Liu, Shan; Ma, Ming-Guo; Ji, Xing-Xiang; Choi, Sun-Eun; Si, Chuanling (Frontiers in Chemistry, 2021)
The kinetics studies is of great importance for the understanding the mechanism of hemicellulose pyrolysis and expanding the applications of hemicellulose. In the past years, rapid progress has been paid on the kinetics studies of hemicellulose hydrolysis. In this article, we firstly introduced the hydrolysis of hemicelluloses via various strategies such as autohydrolysis, dilute acid hydrolysis, catalytic hydrolysis, and enzymatic hydrolysis. Then, the history of kinetic models during hemicellulose hydrolysis was summarized. Special attention was paid to the oligosaccharides as intermediates or substrates, acid as catalyst, and thermogravimetric as analyzer method during the hemicellulose hydrolysis. Furthermore, the problems and suggestion of kinetic models during hemicellulose hydrolysis was provided. It expected that this article will favor the understanding the mechanism of hemicellulose pyrolysis.